Microtubules and Actin Cytoskeleton of Cryptococcus neoformans as Targets for Anticancer Agents to Potentiate a Novel Approach for New Antifungals - Kopecká, Marie (Chemotherapy, 2016)
BACKGROUND: We investigated the targeting of microtubules (MT) and F-actin cytoskeleton (AC) of the human pathogenic yeast Cryptococcus neoformans with agents for cancer therapy, in order to examine whether this yeast cytoskeleton could become a new antifungal target for the inhibition of cell division. METHODS: Cells treated with 10 cytoskeleton inhibitors in yeast extract peptone dextrose medium were investigated by phase-contrast and fluorescence microscopy, and growth inhibition was estimated by cell counts using a Bürker chamber and measuring absorbance for 6 days. RESULTS: Docetaxel, paclitaxel, vinblastine sulfate salt, cytochalasin D and chlorpropham [isopropyl N-(3-chlorophenyl) carbamate] did not inhibit proliferation. The MT inhibitors methyl benzimidazole-2-ylcarbamate (BCM), nocodazole, thiabendazole (TBZ) and vincristine (VINC) disrupted MT and inhibited mitoses, but anucleated buds emerged on cells that increased in size, vacuolated and seemed to die after 2 days. The response of the cells to the presence of the actin inhibitor latrunculin A (LA) included the disappearance of actin patches, actin cables and actin rings; this arrested budding and cell division. However, in 3-4 days, resistant budding cells appeared in all 5 inhibitors. Disruption of the MT and AC and inhibition of cell division and budding persisted only when the MT and AC inhibitors were combined, i.e. VINC + LA, BCM + LA or TBZ + LA. CONCLUSION: The MT and AC of C. neoformans are new antifungal targets for the persistent inhibition of cell division by combined F-actin and MT inhibitors.
Keywords: thiazolidiny; fluorescenční mikroskopie; Actins; mikrofilamenta; Microscopy, Fluorescence; Thiazolidines; buněčné dělení; Microtubules; aktiny; Cell Division; Antifungal Agents; Bridged Bicyclo Compounds, Heterocyclic; Actin Cytoskeleton; Antineoplastic Agents; Cryptococcus neoformans; mikrotubuly; protinádorové látky; Humans; racionální návrh léčiv; bicyklické sloučeniny heterocyklické; Drug Design; lidé; antifungální látky